Integridade da mucosa retal e inflamação em pacientes com retocolite ulcerativa idiopática em atividade - Lopes, Ana Kátia Moura (2022)
Mucosal barrier dysfunction is recognized as a pathogenic factor in ulcerative colitis (UC), and it plays a prominent role in the initiation and progression of the disease. In clinical practices, colonic inflammation associated with UC can be measure by endoscopy and histopathology. The aim of the present study was to assess whether there is a relationship between the impairment of the rectum epithelial barrier and inflammatory damage in patients with UC. We evaluated 10 patients with active UC (Mayo endoscopic score > 1) and 14 control subjects (submitted colonoscopy for colon cancer screening). During the colonoscopy, macroscopic inflammation was evaluated based on the Mayo endoscopic score, and biopsy samples of the rectum were removed to measure microscopic inflammation (Geboes and Robarts scores) and epithelial barrier function (transepithelial electrical resistance). We evaluated 10 patients with active UC (Mayo endoscopic score > 1) and 14 control subjects (submitted colonoscopy for colon cancer screening). During the colonoscopy, macroscopic inflammation was evaluated based on the Mayo endoscopic score, and biopsy samples of the rectum were removed to measure microscopic inflammation (Geboes and Robarts scores) and epithelial barrier function (transepithelial electrical resistance). The colitis group had more endoscopy and microscopic inflammatory damage as compared with the control group. The transepithelial electrical resistance in the rectum was significantly lower (p < 0.05) in patients with active UC when compared with the control group. There is a significantly negative (p < 0.05) correlation between endoscopic inflammation and microscopic damage based on the Geboes scores with transepithelial electrical resistance in the rectum. There are negative correlations between mucosal integrity and inflammatory damage in patients with UC. Further studies are required to assess whether treatment-induced mucosal tissue healing could reverse the damage to the epithelial barrier, providing a potential new therapeutic target for patients with UC.